Comparative Effectiveness of Focused Versus Radial Extracorporeal Shockwave Therapy and Leukocyte-Poor Versus Leukocyte-Rich Platelet-Rich Plasma for Lateral Epicondylitis: A Network Meta-Analysis - Jun Min Cha; Seo Yeon Yoon; Yong Wook Kim; Jong Mi Park; Sang Chul Lee (Journal of Clinical Medicine, 2026)
Background/Objectives: Lateral elbow tendinopathy (LET) causes chronic pain and functional limitation, and the evidence base is confounded by the “lumping” of biologically and physically distinct interventions. We conducted a systematic review and network meta-analysis (NMA) distinguishing focused (fESWT) from radial (rESWT) extracorporeal shockwave therapy (ESWT) and leukocyte-rich (LrPRP) from leukocyte-poor (LpPRP) platelet-rich plasma (PRP) to establish a precise hierarchy of treatment efficacy. Methods: We searched PubMed, EMBASE, Cochrane, Scopus, and Web of Science from inception to 8 December 2025, with the search updated on 12 August 2026. Twenty-three randomized controlled trials (1484 participants) evaluating fESWT, rESWT, LrPRP and LpPRP were included. Standardized mean differences (SMDs) were calculated using a random-effects model, and treatments were ranked by the surface under the cumulative ranking curve (SUCRA). Results: fESWT ranked highest for grip strength overall (SUCRA: 82.6) and in the short term (≤3 months; 78.4). For upper-limb disability (Disabilities of the Arm, Shoulder and Hand), rESWT ranked highest overall (92.9) and in the long term (≥6 months; 94.0), while fESWT ranked lowest (19.9). rESWT was also most effective for pain at rest (Visual Analogue Scale; 86.6) and fESWT for disease-specific function (Patient-Rated Tennis Elbow Evaluation; 81.9), both significantly superior to placebo. The LrPRP advantage did not persist when trials at high risk of bias were excluded. Conclusions: Clinical outcomes in LET are influenced by the specific subtypes of ESWT and PRP. rESWT was most effective for pain at rest and long-term upper-limb function, whereas fESWT was superior for short-term grip strength and disease-specific function. The apparent benefit of LrPRP was less robust and should be regarded as preliminary, and treatment selection should be tailored to a patient’s recovery priorities.